Реактивность кардиоваскулярной системы здоровых лиц при проведении локального холодового теста - Gerasimova-Meigal, L. I.; Gerasimova, M. A.; Sklyarova, A. S.; Sireneva, N. V.; Peskova, A. E.; Meigal, A. Yu. (Патогенез, 2022)
Тезисы конференции